A Case Report of an Elderly Woman With Thrombocytopenia and Bilateral Lung Infiltrates: A Rare Association Between Diffuse Alveolar Hemorrhage and Idiopathic Thrombocytopenic Purpura. Issue 50 (December 2015) - Hashmi, Hafiz Rizwan Talib; Venkatram, Sindhaghatta; Diaz-Fuentes, Gilda
Abstract : Abstract: Etiologies for diffuse alveolar hemorrhage are wide and range from infectious to vasculitis and malignant processes. Idiopathic thrombocytopenic purpura is an autoimmune disorder characterized by persistent thrombocytopenia, with a relatively indolent course in young patients, but a more complicated progression and high associated mortality in the older patients. Diffuse alveolar hemorrhage, complicating idiopathic thrombocytopenic purpura, is a very uncommon association, with only 2 reported cases in the literature. We present a 69-year-old healthy woman presenting with petechial rash, progressive dyspnea, and bilateral alveolar infiltrates. She was found to have idiopathic thrombocytopenic purpura associated with diffuse alveolar hemorrhage. The patient had an excellent response to high doses of pulse steroids and immunoglobulins. A high index of suspicion for noninfectious pulmonary diseases should be considered in patients with autoimmune diseases presenting with pulmonary infiltrates and hypoxia. Flexible bronchoscopy with sequential lavage is a relatively safe procedure in patients with coagulopathy and should be attempted to detect and confirm the diagnosis; absence of hemoptysis should not preclude the diagnosis.